From the Archives of Levon Mkrtchyan. Letters to M. S. Petrovikh 1965–1975 - SAHAKYANC, KARINE (Bulletin of Yerevan University H: Russian Philology, 2021)
The development of the Armenian-Russian literary rela-tions, their expansion and consolidation have been a notable aspect of scientific, literary, organizational activity of distinguished literary critic, academician Levon Mkrtchyan, which has been reflected in his numerous works. Much valuable information in this regard is preserved in L. Mkrtchyan’s rich archive. The letters published in the article represent the way in which one of L. Mkrtchyan’s initiatives was realized, i.e. the first publication of poems of XX century fine lyric poetess and devoted translator of Arme-nian poets Maria Petrovikh, i.e. the book “Dalnee Derevo” published in Yerevan in 1968.